2021
DOI: 10.15562/bmj.v10i2.2403
|View full text |Cite
|
Sign up to set email alerts
|

Chest therapy and breathing exercise in COVID-19 patient: a case report

Abstract: Background: The coronavirus disease (COVID-19) pandemic has several clinical manifestations from asymptomatic to critical condition. Shortness of breath is one of the hallmark symptoms of COVID-19 infection. The main medical management for shortness of breath in COVID-19 infection is oxygen therapy. Physiotherapy and medical rehabilitation such as breathing exercise and chest physiotherapy can be adjuvant therapy that effectively improves breathing effort in COVID-19 patients. This case report will describe br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…Our analysis result found that most of the recommended exercise for post-COVID rehabilitation programs comprises lung rehabilitation [22]. As we know, respiratory complication is the most COVID-19 sequelae found in discharged COVID-19 patients.…”
Section: Discussionmentioning
confidence: 71%
“…Our analysis result found that most of the recommended exercise for post-COVID rehabilitation programs comprises lung rehabilitation [22]. As we know, respiratory complication is the most COVID-19 sequelae found in discharged COVID-19 patients.…”
Section: Discussionmentioning
confidence: 71%
“…For the pursed lip breathing, the patient was instructed to breathe in slowly and deeply through the nose and then exhale gently through pursed lips using instructions: blow on the candle flame, without dousing it and avoid forceful expiration and inspiration) and for diaphragmatic breathing, the patient was instructed to sit comfortably, with knees bent and head, neck and shoulders in relaxed position. Place one hand on the upper chest and the other just below the rib cage and feel the movement of the diaphragm while breathing with instructions: slowly breathe in through the nose and feel the stomach moving out against the hand placed below the rib cage and slowly breathe out through pursed lips [ 10 ].…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Os exercícios respiratórios e terapias torácicas têm por finalidade favorecer a expansão torácica total e a boa mobilidade pulmonar, otimizando a oxigenação, as trocas gasosas, o processo de perfusão e difusão sanguínea. Espera-se que ao aplicar esses conceitos no tratamento pulmonar, por meio do aplicativo FISIOAR I, os efeitos sejam os mesmos, por se tratar da mesma conduta (Prabawa, et al, 2021).…”
Section: • Exercícios Respiratóriosunclassified